Public Communication Of The Indonesian Government In Handling Flash Flood Disaster In Sumatra - Selamat Ginting (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study aims to examine the public communication of the Indonesian Government in handling the flash flood disaster in Sumatra, at the end of 2025. The theory used in this study is the Situational Crisis Communication Theory (SCCT), developed by W. Timothy Coombs, with two assumptions, namely crisis response strategy, and crisis responsibility. The method used is a desk study, by tracing several keywords: government public communication; disaster management; flash flood; through searching Scopus Elsevier, Springer, Taylor & Francis journals, print and electronic media coverage during the Sumatra flash flood disaster, from November 24, 2025 to January 15, 2026, impacts, losses, recovery, and especially the stages in the Indonesian Government's handling of the Sumatra flash flood disaster. The results of the study indicate that the current Prabowo Government does not yet have a measurable, integrated and planned disaster management procedure. This has resulted in inadequate Public Communication, especially in disaster management such as that which occurred in Sumatra. SCCT analysis shows that the Prabowo administration is employing a recovery strategy through apologies, although the exact compensation and corrective actions are unclear. In terms of public communication, the Prabowo administration is still considered slow, uncoordinated, and lacks specific guidelines, particularly for disaster management, particularly the flash floods in Sumatra.